Nyctocalos tunjuharii (Bignoniaceae), a new species from Sabah, Malaysian Borneo - Berhaman Ahmad (Naturalis Biodiversity Center, 2023)
Nyctocalos tunjuharii (Bignoniaceae) is described and illustrated as a new species from Mt Kallang, Tenom, Sabah, Malaysian Borneo. It is distinguished from N. cuspidatus by its longer, linear calyx teeth, shorter corolla tube and included stamens that reach less than half the length of the upper dilated part of the corolla tube. This species is restricted to an area near Mt Kallang, Tenom, Sabah. A preliminary conservation status assessment is presented and a key to the Malesian taxa is provided.